Penguatan Literasi Dan Pencatatan Keuangan Pada Kelompok UMKM Perempuan Mandiri di Sidoarjo - Ratna Anggraini Aripratiwi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Micro, Small and Medium Enterprises (MSMEs) are one of the pillars supporting the Indonesian economy and are able to contribute to Indonesia's Gross Domestic Product (GDP) by 61.07%. This strategic role is what drives the Government to focus on programs to support MSMEs to be more sustainable. One example of a program developed by the Government is the Kurma Independent Women's Business Card Program (KURMA) in Sidoarjo Regency. Many obstacles faced by MSMEs certainly depend on the type of business, location, inadequate understanding of human resources, and minimal financial literacy. Financial literacy is one of the problems of business actors, especially MSMEs. This service focuses on the MSME Women's group who have received the KURMA assistance program. The service method used is Participatory Action Research (PAR), which is an active collaboration between the community and researchers to find program solutions to problems. The results of this service show several positive impacts, including increasing awareness of MSME entrepreneurs of the importance of understanding financial literacy and preparing business financial reports, the mentoring process helps entrepreneurs in preparing financial reports, and providing added value to MSMEs. This service provides a reflection of changes in the development and sustainability of SMEs.